2019
DOI: 10.15294/kemas.v15i2.19255
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Early Symptoms Related to Respiratory Disease in Pedicab Drivers in Surabaya

Abstract: Various factors which cause respiratory diseases such as smoking, air pollution, and disease history are found in pedicab. The purpose of this study was to understand the risk factors and early symptoms that related to respiratory disease in pedicab drivers. This study used observational cross-sectional design with purposive sampling. Variables that were recorded in this study were lung function risk factors and early symptoms of respiratory disorders. The number of samples was 148 respondents (135 with respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
4
0
7
Order By: Relevance
“…In clinical guidelines, pulmonary function interpretation has historically been based on the most important anthropometric factors, including weight, height, sex, and age [27]. In Lorensia et al [28], in 148 respondents pedicab drives as high risk chronic pulmonary disease (135 with respiratory disorder and 13 without respiratory disorder). The results of this study found the most common risk factor was air pollution exposure.…”
Section: Research Results Knowledgementioning
confidence: 99%
“…In clinical guidelines, pulmonary function interpretation has historically been based on the most important anthropometric factors, including weight, height, sex, and age [27]. In Lorensia et al [28], in 148 respondents pedicab drives as high risk chronic pulmonary disease (135 with respiratory disorder and 13 without respiratory disorder). The results of this study found the most common risk factor was air pollution exposure.…”
Section: Research Results Knowledgementioning
confidence: 99%
“…Terdapat hubungan yang signifikan antara derajat merokok dengan derajat keparahan PPOK, dan korelasi yang kuat antara keduanya. 4 Merokok tembakau merupakan faktor risiko terbesar dari PPOK, yang memiliki prevalensi yang besar dari gejala respiratori dan abnormalitas fungsi paru dengan penurunan FEV1 dan mortalitas dibandingkan non-perokok. Perokok pasif atau dikenal dengan environmental tobacco smoke (ETS) dapat berkontribusi terhadap gejala respiratori dan PPOK dengan peningkatan total paparan partikel dan gas.…”
Section: Pembahasanunclassified
“…Berdasarkan data yang diperoleh dari Riset Kesehatan Dasar (2013), PPOK memiliki prevalensi 3,7% per satu juta penduduk di Indonesia.2 PPOK menjadi seperti bom waktu di Indonesia, karena banyak kondisi masyarakat dengan risiko PPOK sangat tinggi dengan gangguan fungsi paru namun belum menyadarinya. 3,4 PPOK merupakan penyakit kronis yang membutuhkan terapi jangka panjang. Pengobatan sintetis tidak selalu aman, dan sering menimbukan efek tidak dikehendaki, 5,6,7 dan ketidakpatuhan pengobatan.…”
unclassified
“…Perkerjaan ini dapat dikategorikan beresiko karena para pengemudi becak selalu mendapat paparan polusi dan terlebih lagi sebagian besar adalah perokok aktif. 15 Oleh karena itu diharapkan pada penelitian ini dapat mengetahui seberapa besar tingkat pengetahuan pengemudi becak, sehingga dapat memberikan gambaran secara tepat. Vitamin D berperan penting dalam pemeliharaan fisiologi dan kesehatan.…”
Section: Pendahuluanunclassified